(untitled) (CAHIERS MAGELLANES-NS, 2024)
The nanofibers have attained significance due to their exclusive characteristics such as high porosity, enhanced surface area, and outstanding mechanical features in comparison to the other materials. The increased surface to volume ratio, biodegradability, and biocompatibility of nanofibers elevates its significance in biomedical and pharmaceutical sciences. The potentiality of nanofibers in drug targeting and controlled drug delivery has increased the patient compliance with reduced side effects and systemic toxicity. Nanofibers have revolutionized the field of bioscience by amplifying therapeutic outcomes through their superior pharmacokinetic and pharmacodynamic profiles. Their unmatched versatility makes them a valuable asset in modern medicine. The drug delivery mechanism relies on several mechanisms such as drug loading techniques, polymeric interactions, polymer swelling, and the nature of polymer degradation or erosion. The comprehensive review summarized the latest technical advancements in the production of nanofibers and their cutting-edge applications in the biomedical field. Furthermore, the groundbreaking review sheds light on the game-changing potential of nanofibers with pre-defined quality attributes and its remarkable development has opened up new avenues of research and healthcare possibilities for professionals. The superior formulation techniques render an efficient approach to deliver the optimized drug concentrations at the targeted site and ensure a faster recovery with significant therapeutic outcomes.